K-Means Based Fingerprint Segmentation with Sensor Interoperability. (6th May 2010) - Yang Yang, Gongping Gongping; Zhou Zhou, Guang-Tong Guang-Tong; Yin Yin, Yilong Yilong; Yang Yang, Xiukun Xiukun
Abstract : A critical step in an automatic fingerprint recognition system is the segmentation of fingerprint images. Existing methods are usually designed to segment fingerprint images originated from a certain sensor. Thus their performances are significantly affected when dealing with fingerprints collected by different sensors. This work studies the sensor interoperability of fingerprint segmentation algorithms, which refers to the algorithm's ability to adapt to the raw fingerprints obtained from different sensors. We empirically analyze the sensor interoperability problem, and effectively address the issue by proposing a k -means based segmentation method called SKI. SKI clusters foreground and background blocks of a fingerprint image based on the k -means algorithm, where a fingerprint block is represented by a 3-dimensional feature vector consisting of block-wise coherence, mean, and variance (abbreviated as CMV). SKI also employs morphological postprocessing to achieve favorable segmentation results. We perform SKI on each fingerprint to ensure sensor interoperability. The interoperability and robustness of our method are validated by experiments performed on a number of fingerprint databases which are obtained from various sensors.